Transient Tachypnea of Newborn in Neonatal Care Unit of Children Welfare Hospital Medical City /Baghdad - Hameed, Numan N.; Naaom, Manal B.; Shareef, Ali J. (Journal of the Faculty of Medicine Baghdad, 2015)
Background: Transient tachypnea (TTN) is a common disorder of the newborn. It is characterized by the early onset of tachypnea sometimes with retractions or expiratory grunting and occasionally cyanosis that is relieved by minimal oxygen supplementation (<40%). Objectives: To identify the risk factors and describe the clinical characteristics, treatment and outcome of infants with TTN. Patients and methods: This study was carried out on 100 newborn babies with birth weight of 2500 to 4000 gm and gestational ages range from (completed 37 -42 wks), who were admitted to the neonatal care unit of Children Welfare Teaching Hospital, Medical city, Baghdad, from 1st of September 2013 to the 31st of January 2014, and diagnosed as having TTN. Results: Males represented 68% and females were 32%, with a male to female ratio of 2.1:1. Fifty-three percent aged 38 weeks, compared to 38% aged < 38 weeks and 9% > 38 weeks, indicating that there was a significant inverse correlation between the incidence of TTN and the gestational age. There was a highly significant inverse correlation between the neonate’s weight and the frequency of TTN. Cesarean section done in 80% compared to 20% delivered with spontaneous vaginal delivery (SVD) and neonates who were delivered by elective section were more likely to have TTN than those delivered with SVD or emergency section. The history of maternal diabetes in (17%), a statistically significant association was found between TTN and the maternal Diabetes Mellitus but not with other maternal diseases. Tachypnea and chest retraction were the most frequent clinical manifestations, 93% and 72% respectively. Chest X-ray revealed that 71% had increased pulmonary vascular markings, over aeration in 22%. Out of the 100 cases, 95% were discharged after they improved without complications, 5% complicated with Pneumothorax. No death in the studied group. Conclusions: There was a significant association between TTN and maternal diabetes, mode of delivery especially elective CS, lower gestational age (38 weeks and less), and lower body weight. The most frequent clinical manifestations of TTN are Tachypnea and chest retraction. Increased pulmonary vascular markings and over- aeration are the most frequent radiological manifestations. TTN is a self-limited disease in most of the cases.